Adenomatoid odontogenic tumor in anterior maxilla: A case report (Indian Journal of Case Reports, 2024)
Adenomatoid odontogenic tumor (AOT) is an uncommon benign lesion of odontogenic origin. This tumor mainly affects young individuals in the second decade with a female predilection and is most commonly located in the anterior maxilla, usually associated with an impacted canine tooth. The aim of this report is to discuss the case of a 24-year-old female with AOT in the maxillary incisor region and includes the surgical management of the case.